Teaching and learning in an undergraduate business context: an inquiry into lecturers' conceptions of teaching and their students' conceptions of learning - Varnava-Marouchou, Despina (2008)
During one of the many discussions that I often have with my classes, it became apparent to me that some students had varied views regarding teaching and learning. In fact, what was basically a good teaching practice to me, apparently to many of my students it was not so. At the same time, in the last few years lecturers began expressing their disappointment concerning their students' outcomes and their evident lack of interest as regards their introductory courses.